DAMPAK PERTUMBUHAN EKONOMI, KONTROL KORUPSI, DAN YIELD TERHADAP INVESTASI ASING DI PASAR SUN - Wahyu Tri Rahmawati; Willem A. Makaliwe (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2021)
ABSTRACT Foreign investment in debt securities in Indonesia continues to grow. Foreign investor ownership in Government Securities (SUN) reached 39% at the end of 2019 from initially only less than 1% at the end of 2002. Foreign investor hold the largest ownership in tradable Government Securities. This study discusses the push and pull factors of foreign portfolio in debt securities investment in emerging markets and Indonesia on the period of 2000-2017. This research uses quantitative methods with panel data analysis. The results showed that economic growth, corruption control, dan financial openness were the main pull factors for foreign investment in debt instruments in emerging markets. Low yield in developed countries was the push factor of foreign investment in debt securities into emerging markets. In addition to economic growth and corruption control, yield on local debt instruments attract foreign investment in debt securities in Indonesia. The results showed that the yield on local debt securities have a negative effect on foreign investment in Indonesian debt securities so that the government does not need to provide too high yield on Government Securities.